Impact of transport layer protocols on the efficiency of special purpose radio-communications - Nedeljković, Ljubiša S. (Vojnotehnički glasnik / Military Technical Courier, 2013)
The efficiency of special purpose radio-communications depends on transport layer protocols. Meny factors have an impact on special purpose radio-communications efficiency, as well as TCP and UDP protocols. This paper presents the transport protocols throughput analysis in the HF and VHF radio-communications with promis RTT and packet error rate probability. This paper considers a posibility of the application of TCP and UDP protocols in special purpose radio-communications. The following factors will be considered: RTT, Round Trip Time, data packet size, window size and bit error rate. It can be seen from the analysis which transport protocol is the most suitable for special purpose radio-networks. TCP throughput The TCP is a connection-oriented protocol with a capability of retransmissions and acknowledgement. The TCP protocol throughput versus Round Trip Time and windows size has been considered. The TCP throughput depends on RTT - when the RTT increases, then the throughput decreases. The RTT has a value up to 9s. Then the article considers the TCP throughput versus the packet error rate, where for a maximum bit error rate of 10-3 the TCP throughput is very bad. The BER valuesof more than 10-3 are not apropriate for the TCP, since the throughput is then very small. UDP throughput The UDP is the other transport layer services alternative. The UDP is a connectionless protocol with error detection. The UDP troughput depends on overhead bits and the type of modulation.The UDP has fewer overhead (nondata) bits than the TCP, header 8 B and IP header 20 B. The UDP throughput is close to the equal transsmision rate of the physical layer. Performance comparation between the TCP and the UDP in the tactical radio-network TCPs are successful when the BER is from 10-5 to 10-6. If the RTT is longer than 10-3 , the TCP will be dificult to operate. A delay in the HF and VHF radio-communications may be long and the TCP throughput is very slow. When the RTT is shorter than 0.3 s, the TCP throughput is good. If the RTT increases beyond 1s, the TCP throughput rapidly decreases. The UDP is a connectionless protocol, without acknowledgement. The UDP protocol is independent of the RTT due to its connection-less behavior, i.e. due to the abdication od reverse link acknowledgement signalling. The UDP throughput is approximately sam percent less than the physical throughput due to the overhead. Conclusion The TCP is not a suitable transport protocol for special purpose radio-communications with large amounts of bit-error rate and long RTT. Its throughput in that condition will be small. The performance of the UDP protocol in special purpose radio-communications is better than the performance of the TCP protocol. Its thrughput is independent of the RTT due to its connection-less behavior. The UDP is suitable for the transport protocol for special purpose radio-communications.